Tracing dsDNA Virus-Host Coevolution through Correlation of Their G-Quadruplex-Forming Sequences - Bohálová, Natália; Cantara, Alessio; Bartas, Martin; Kaura, Patrik; Šťastný, Jiří; Pečinka, Petr; Fojta, Miroslav; Brázda, Václav (International journal of molecular sciences, 2021)
The importance of gene expression regulation in viruses based upon G-quadruplex may point to its potential utilization in therapeutic targeting. Here, we present analyses as to the occurrence of putative G-quadruplex-forming sequences (PQS) in all reference viral dsDNA genomes and evaluate their dependence on PQS occurrence in host organisms using the G4Hunter tool. PQS frequencies differ across host taxa without regard to GC content. The overlay of PQS with annotated regions reveals the localization of PQS in specific regions. While abundance in some, such as repeat regions, is shared by all groups, others are unique. There is abundance within introns of Eukaryota-infecting viruses, but depletion of PQS in introns of bacteria-infecting viruses. We reveal a significant positive correlation between PQS frequencies in dsDNA viruses and corresponding hosts from archaea, bacteria, and eukaryotes. A strong relationship between PQS in a virus and its host indicates their close coevolution and evolutionarily reciprocal mimicking of genome organization.
Keywords: Gene Expression Regulation; coevolution; virus; G4Hunter; Viruses; Genome, Viral; výpočetní biologie; virové proteiny; viry; Bacteria; dsDNA; host; bioinformatics; G-Quadruplexes; Viral Proteins; genom; lidé; Archaea; Humans; regulace genové exprese; G-quadruplex; DNA; genom virový; Genome; G-kvadruplexy; Computational Biology